Implikasi Putusan Mahkamah Konstitusi Nomor 93/PUU-X/2012 Bagi Penyelesaian Sengketa Bisnis dan Keuangan Syariah - Umam, Khotibul (Mahkamah Konstitusi Republik Indonesia, 2015)
The Decision of Constitutional Court No. 93/PUU-X/2012 regarding Judicial Review of Law No. 21/2008 regarding Sharia Banking with the Indonesian Constitution 1945 was giving a strong statement that the explanation of this a quolawhas a potential impact to arise legal uncertainty and legal confuse, meanwhile Article 55 in the whole still conform with the Constitution. The juridical implication from this a quodecision, i.e. The tribunal of District Court have to state if they have no authority to settle the case in sharia banking, althought it has been agreed in an akad (agreement). It has been stressed with the nature of Constitutional Court Decision “final and binding” and also bind all of citizens (erga omnes). Then, the opportunity to implement of its decision to sharia businees and financial institutions exist based on analogy, esp argumentum a fortiory. The expectation, it will give legal certainty in the context of Judicial that has an authority to settle the potential dispute between customer and sharia business and financial institutions.